2008
DOI: 10.1002/elps.200800178
|View full text |Cite
|
Sign up to set email alerts
|

Boronate affinity saccharide electrophoresis: A novel carbohydrate analysis tool

Abstract: The incorporation of specialised carbohydrate affinity ligand methacrylamido phenylboronic acid in polyacrylamide gels for fluorophore-assisted carbohydrate electrophoresis greatly improved the effective separation of saccharides that show similar mobilities in standard electrophoresis. Polyacrylamide gel electrophoresis using methacrylamido phenylboronic acid in low loading (typically 0.5-1% dry weight) was unequivocally shown to alter retention of labelled saccharides depending on their boronate affinity. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 28 publications
0
33
0
Order By: Relevance
“…Following the successful development of a new boron affinity based electrophoresis tool for carbohydrates 21, improving the separation of saccharides, it was reasoned that inclusion of boronic acid saccharide receptors that reversibly interact with saccharides could also be used to analyze carbohydrates attached to proteins and may advantageously affect their retention characteristics. Again we have chosen a phenyl boronic acid because of its capacity to function as saccharide receptors in aqueous solution, as previously attested by the many sensory systems reported 26–30, thereby forming cyclic boronic esters with a variety of carbohydrates under equilibrium conditions, via reversible covalent interactions in aqueous media (see also 21).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the successful development of a new boron affinity based electrophoresis tool for carbohydrates 21, improving the separation of saccharides, it was reasoned that inclusion of boronic acid saccharide receptors that reversibly interact with saccharides could also be used to analyze carbohydrates attached to proteins and may advantageously affect their retention characteristics. Again we have chosen a phenyl boronic acid because of its capacity to function as saccharide receptors in aqueous solution, as previously attested by the many sensory systems reported 26–30, thereby forming cyclic boronic esters with a variety of carbohydrates under equilibrium conditions, via reversible covalent interactions in aqueous media (see also 21).…”
Section: Resultsmentioning
confidence: 99%
“…Here we present a simple technique, based on a widely used method for protein analysis, PAGE, for the analysis of early as well as late non‐enzymatic carbohydrate modifications in proteins. The presented methacrylamido phenylboronate acrylamide gel electrophoresis (mP‐AGE) method, initially designed for the separation of carbohydrates 21 has here been adapted to specifically detect, analyze and separate early (Amadori) as well as long‐term (AGE) glycation products from unaffected proteins.…”
Section: Introductionmentioning
confidence: 99%
“…We are currently engaged in a program of research utilising boronic acids in polymer constructs [1], and wanted to rapidly access a range of phenylboronic acid methacrylamides, exemplified by 1a-c, Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…In order to provide a simple, cost-effective detection and analysis tool for glycated proteins, we recently developed an electrophoresis based method using polyacrylamide incorporated with the carbohydrate affinity ligand methacrylamido phenylboronic acid (MPBA)16. We first tested this technique on simple carbohydrates and showed that by using the same basic principle as BAC, exploiting the reversible covalent interaction between boronic acid and cis -diols1718, the MPBA-incorporated acrylamide gels enabled the improved separation of saccharides, and the differentiation between monosaccharides and dissacharides.…”
mentioning
confidence: 99%